A Study of the Technical Aspects of Local Buffalo Rearing in West Aceh Regency - Gaznur, Zikri Maulina; Syafiq, Wan Taufiq Aulia; Koesmara, Hendra; Sari, Eka Mutia; Abdullah, Mohd Agus Nashri; Asril, Asril (Syiah Kuala University, 2024)
The research problem is whether the technical aspects of raising buffalo livestock in West Aceh Regency have been implemented properly and correctly in accordance with the DITJENNAK guidelinesof 1992by buffalo breeders in West Aceh Regency.This research aims to examine theimplementation oftechnical aspects of local buffalo rearing in West Aceh Regency. The research locations covered 25 villages(5 villageseach district), namelyin5 villages Johan Pahlawan,Mereubo,Kaway XVI and Samatiga District. This study used a survey method of 100 buffalo breeders using a questionnaire.The parameters were1)aspects of breeding and reproduction,2)food, maintenance management,3)health,4)cages and equipment. The sampling technique is random and the number of samples is determined deliberately taking into consideration the breeders who are willing to be interviewed. The data obtained is processed by calculating the percentage score and then compared with the categories set by the Directorate General of Livestock (1992). The results showed that the implementation of the technical aspects of raising buffalorearingin West Aceh District was 41.71%,including the application of technical aspects of breeding and reproduction 57.72%, aspects of food13.74%,aspects of maintenance management 38.58%, health aspects 67.27%, cage and equipment aspects 52.09%. It can be concluded that the implementation of technical aspects of buffalo farming in West Aceh Regency is poor category with the guidelines of the Directorate General of Livestock (1992). From these results it is recommended that the technical aspects of buffalo rearing in West Aceh Regency should be improved in the future.